The Influence of Total Rewards Approach to Employees Sales Performance in Bersatu Sukses Group - Gofelin Steifi Karundeng; Damelina Basauli Tambunan (International Journal of Review Management Business and Entrepreneurship (RMBE), 2021)
This study aims to analyze whether the six aspects of total rewards approach – performance and career management, quality work environment, work and/or home integration, base pay, benefits, and contingency pay – affect employees’ sales performance. This research uses the population of Bersatu Sukses Group sales marketers with total of 105 people. Purposive sampling method was used for this research through simple random sampling technique, which led to a sample size of 83. This research used multiple regression to analyze the measure of relationship between the variables. Based on the results of the analysis, total rewards approach – performance and career management, quality work environment, work and/or home integration, base pay, benefits, and contingency pay – have significant and positive effects to employees’ sales performance at Bersatu Sukses Group. Work and/or home integration also proved to have the greatest impact of the six variables to employee’s sales performance with its heightened productivity brought by the variable as the most favored indicator by the average of the respondents. Furthermore, from the six total rewards approach, benefits and contingency pay are two variables with the least influence on employees’ performance in sales of Bersatu Sukses Group.